The Determinants of Stunting for Children Aged 24-59 Months in Kulon Progo District 2019 - Hendraswari, Chatrine Aprilia; Purnamaningrum, Yuliasti Eka; Maryani, Tri; Widyastuti, Yani; Harith, Sakinah (UI Scholars Hub, 2021)
This study pertains to stunting in children in Indonesian with z-scores of less than -2 Standard Deviation (SD) and less than -3 SD. The preliminary study results showed the highest prevalence of stunting to be 22.6%, at the Temon II Primary Health Care in Kulon Progo District. The study aimed to assess the determinants of stunting children aged 24–59 months. This study was conducted from September 2018–May 2019. The design of this study was analytical observational with study design case-control. The sample was 60 children aged 24–59 months. The method utilized proportional sampling, whereas the data analysis applied chi-square and logistic regression.The analysis of statistical tests showed a significant correlation between the stunting children and energy intake factor (p-value = 0.030; α = 0.05; CI = 95%). Risk factors were energy intake, protein intake, suffering from acute respiratory tract infections, and suffering diarrhea. A non-risk factor was immunization status. Protective factors were access to clean water and the history of exclusive breastfeeding. The most influential factor for stunting children aged 24–59 months was energy intake.